Reconstructing Recent Paradigm Through the Interpretation of Halal Consumption with Shifting Paradigm Theory - Assa'idi, Sa'dullah (Dialogia, 2023)
The obligation to consume halal food and beverages was originally an implementation of religious values in life. However, now, these values have been systematized in such a way as to gain profit by Moslems themselves and non-Muslims. The old paradigm of halal food is generally measured through the limits of unlawful food and drinks in the Qur'an and Hadith. The knowledge of society about unlawful food and drinks forms an understanding that other than the forbidden food means halal to consume. However, this paradigm clashes with recent science and technology, which prove that halal foods can be haram because of the processes carried out on the food or any external factors. This encourages various parties to form a new paradigm about the halal concept. This research is a descriptive-analytical library research to clearly describe the data on various paradigms in halal studies and analyze the anomalies in old studies that have moved various groups to form a new paradigm. This study uses the shift paradigm theory by Thomas Kuhn, which consists of pre-paradigm, normal phase, crisis or anomaly phase, and new paradigm shift phase. The data in this study are divided into primary and secondary data; the primary data of this study is the old paradigm in the interpretation of QS. Al-Baqarah [2]: 168, and secondary data in this study come from books, scientific journals, theses, dissertations, and others. The results of this study indicate that the interpretation of QS. Al-Baqarah [2]: 168 needs to be developed again because the old interpretation cannot solve the problems that arise in the current era. In forming a new paradigm, the government of the Republic of Indonesia commodifies the halal value of religion. It implements the JPH Law as a new standard that is more specific and systematic in determining halal products. Research like this is interesting to find new solutions to every social problem from various scientific backgrounds.